A new genus of Afrotropical Lasiocampini: Revaya gen. n. (Lepidoptera, Lasiocampidae, Lasiocampinae) - Prozorov, Alexey M.; Prozorova, Tatiana A.; Yakovlev, Roman V.; Volkova, Julia S.; Saldaitis, Aidas; Sulak, Harald; Revay, Edita E.; Müller, Günter C. (Zootaxa, 2023)
A new genus Revaya gen. n. with Revaya yahya sp. n. (type-species) and Revaya edita sp. n. are described. A detailed diagnosis for the new genus is provided and compared with three closely related genera: Catalebeda Aurivillius, 1902; Ptyssophlebia Berio, 1937; and Oplometa, Aurivillius 1894. Male genitalia of Oplometa cassandra (Druce, 1887) and female genitalia of Ptyssophlebia discocellularis (Strand, 1912) are illustrated for the first time. Catalebeda producta, P. discocellularis and O. cassandra are recorded for the first time in the Democratic Republic of the Congo.